Effect of Leg Dominance on Medium- to Long-Term Functional Outcomes, Quality of Life, and Revision Rates After Isolated ACL Reconstruction. Issue 4 (8th April 2021) - Uzun, Erdal; Misir, Abdulhamit; Guney, Ahmet
Background: The effect of leg dominance on short-term functional outcomes and return to sports after arthroscopic anterior cruciate ligament reconstruction (ACLR) has been evaluated. However, postoperative medium- to long-term recovery and revision rates are not well known. Purpose: To investigate whether leg dominance affects medium- to long-term clinical and functional scores and revision rates after ACLR. Study Design: Cohort study; Level of evidence, 3. Methods: Included in this study were 235 patients (205 male and 30 female) who underwent isolated arthroscopic ACLR. Patients were divided according to the leg dominance status of their injured limb into 2 groups: dominant leg injured (120 patients) and nondominant leg injured (115 patients). Preoperative and postoperative functional outcomes and health-related quality of life (HRQoL) were evaluated using the visual analog scale for pain, Tegner activity scale, Lysholm knee score, International Knee Documentation Committee (IKDC) subjective knee evaluation form, 36-Item Short Form Health Survey (SF-36), and overall patient satisfaction. Moreover, the revision rates of the 2 groups were compared according to leg dominance, patient characteristics, and operative features. Results: The mean follow-up period was 8.0 ± 2.3 years (range, 5-13 years). A significant preoperative to postoperative improvement in range of motion and functional scores was noticed in both groups ( P < .001 for all). However, the improvement was significantly higher in the dominant leg group for the Tegner ( P = .001), Lysholm ( P = .006), and IKDC ( P < .001) scores as well as for the SF-36 domain scores for general health ( P = .009), social role ( P = .048), and emotional role ( P = .032). Also, patient satisfaction was significantly higher in the dominant leg group ( P = .007). The dominant leg group was associated with a lower revision rate compared with the nondominant leg group (5.8% vs 15.7%, respectively; P = .015). Conclusion: High recovery rates were seen after arthroscopic ACLR, regardless of leg dominance. However, leg dominance had a significant effect on postoperative medium- to long-term functional outcomes, HRQoL, and revision rates.